Pengembangan Kegiatan Rumah Baca Tiara Veritas Cikande (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2022)
The development of activities carried out at the Tiara Veritas Cikandem reading house is a continuation of the development of the reading house which has undergone renovations both in terms of buildings and available reading books. The development of this activity aims to develop interest in reading for children of learning age; cultivate reading literacy in the environment around the Tiara Veritas Cikande reading house; and obtain parental support in the reading development of children of learning age. The methods used include: guided and independent reading training for children of learning age, training for parents on how to read the correct story to children; and training for local residents who are still illiterate. The objects in the development of Tiara Veritas Cikande reading house activities are children of learning age (PAUD and SD) around 30-40 children, parents of children of learning age, and local residents. The place of implementation is the Tiara Veritas Cikande reading house. The results obtained are the enthusiasm of children of learning age who always come to read at the Tiara Veritas Cikande reading house and the support of parents who strongly support the existence of the Tiara Veritas Cikande reading house.